Genetic Variability and Inter-relationship between Yield and Yield Components in Jhum Rice (Oryza sativa L.) Genotypes of Khagrachhari District in Bangladesh (The Agriculturists, 2020)
The present investigation consists of 47 rice genotypes and the experiment was conducted during Aus season, 2016 in Randomized Block Design with three replications. The data were recorded for 13 quantitative characters to study genetic variability, heritability, genetic advance, correlation coefficient analysis and path analysis. Analysis of variance among 47 genotypes showed a significant difference for all characters studied. The highest genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) were observed for grain yield followed by the number of effective tillers, the number of filled grains per panicle and 1000 grain weight indicating that these characters could be used in selection for the crop improvement program. High estimates of heritability was observed for grain yield, grain length, plant height, number of filled grain per panicle, 1000 grain weight and days to 50% flowering. High genetic advance was observed for the number of filled grains per panicle and plant height, indicating predominance of additive gene effects and possibilities of effective selection for the improvement of these traits. Grain yield showed positive association with number of effective tiller and number of filled grain per panicle at genotypic in conjunction with phenotypic level. Days to maturity possessed the highest positive direct effect and significant indirect correlation with yield.The Agriculturists 2020; 18(1) 01-09